2021
DOI: 10.1021/acscatal.1c02947
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Regio- and Enantioselective Hydroallylation of 1-Trifluoromethylalkenes: Effect of Crown Ether

Abstract: A Cu-catalyzed regio- and enantioselective hydroallylation of 1-trifluoromethylalkenes with hydrosilanes and allylic chlorides has been developed. An in situ generated CuH species undergoes the hydrocupration regio- and enantioselectively to form a chiral α-CF3 alkylcopper intermediate, which then leads to the optically active hydroallylated product. The key to success is the use of not only an appropriate chiral bisphosphine ligand but also 18-crown-6 to suppress the otherwise predominant β-F elimination from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…In 2019, pioneering studies from the groups of Hirano/Miura, and Hoveyda demonstrated Cu-based protocols for hydroamination and protoborylation of trifluoromethylalkenes, respectively (Scheme ). More recently, a Cu-catalyzed enantioselective hydroallylation of trifluoromethylalkenes was disclosed by Hirano’s group . These researchers found that Lewis acidic alkaline cation (Li + , Na + , K + , and Cs + ) was conducive to the success of these transformations.…”
mentioning
confidence: 99%
“…In 2019, pioneering studies from the groups of Hirano/Miura, and Hoveyda demonstrated Cu-based protocols for hydroamination and protoborylation of trifluoromethylalkenes, respectively (Scheme ). More recently, a Cu-catalyzed enantioselective hydroallylation of trifluoromethylalkenes was disclosed by Hirano’s group . These researchers found that Lewis acidic alkaline cation (Li + , Na + , K + , and Cs + ) was conducive to the success of these transformations.…”
mentioning
confidence: 99%
“…The same authors subsequently developed a related Cucatalyzed asymmetric hydroallylation with allylic chlorides 61 instead of hydroxylamines 56 (Scheme 20). 46 In this case, the use of 18-crown-6 was crucial for the disruption of Cs-F interactions 47 to suppress the undesired -F elimination. This is one of the few successful examples of the catalytic asymmetric construction of non-allylic and non-benzylic CF 3 -substituted sp 3 chiral carbon centers.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…Following precedents in enantioselective Cu-catalyzed 1,2-addition across activated alkenes, Hirano and co-workers reported a regio-and enantioselective hydroallylation of 1-trifluoroalkenes. 46 The observed chemo-and regioselectivity of the hydride addition hinged on the strongly activated and polarized terminal trifluoroalkene, which directd the Cu-hydride addition exclusively to the olefinic carbon C(β) to CF 3 . By using an appropriate chiral bidentate phosphine ligand, enantiomerically pure α-CF 3 Recent efforts in Cu-catalyzed allylic substitution have been directed toward the formation of nucleophilic copper(I) species in situ intermediates.…”
Section: Reactionsmentioning
confidence: 99%
“…The introduction of CF 3 -bearing stereogenic centers without any proximal heteroatoms or allylic moieties remains a synthetic challenge. Following precedents in enantioselective Cu-catalyzed 1,2-addition across activated alkenes, Hirano and co-workers reported a regio- and enantioselective hydroallylation of 1-trifluoroalkenes . The observed chemo- and regioselectivity of the hydride addition hinged on the strongly activated and polarized terminal trifluoroalkene, which directd the Cu-hydride addition exclusively to the olefinic carbon C­(β) to CF 3 .…”
Section: Recent Reports On Cu-catalyzed Reactionsmentioning
confidence: 99%